Asleep surgery for deep brain stimulation of the globus pallidus internus in pediatric dystonia associated with KMT2B mutation - Chingiz Nurimanov; Karashash Menlibayeva; Seitzhan Aidarov; Iroda Mammadinova; Nurtay Nurakay (Annals of Movement Disorders)
Pediatric dystonia refers to the onset of dystonia before the age of 21 years. Accurate diagnosis through genetic testing and precise electrode placement may significantly improve motor symptoms and quality of life of patients with gene-associated dystonia. This report presents a rare KMT2B-related dystonia case managed with bilateral pallidal deep brain stimulation (DBS) in an 8-year-old girl. The patient presented with muscle contractions on the distal parts of the lower limbs, speech impairment, and myoclonic jerking movements. Genomic sequencing identified a heterozygous mutation in the KMT2B gene (617284 on chromosome 19p13). In this case, DBS of the globus pallidus internus was performed under general anesthesia. Six months post-surgery, the Burke–Fahn–Marsden scale scores indicated a 46% improvement, and the scores for the Unified Dystonia Rating Scale and Global Dystonia Severity Rating Scale showed 50% and 28% improvements, respectively. Accurate diagnosis of KMT2B-related dystonia holds significant value in terms of guiding appropriate treatment as the disease is responsive to DBS surgery targeting the globus pallidus internus. This case illustrates the benefits of DBS in pediatric patients and its role in advancing surgical interventions for dystonia.